Faktor-Faktor Yang Mempengaruhi Pergerakan Dari Singkil ke Pulau Banyak Dengan Transportasi Air - Irma Dewi (Jurnal Ilmiah Telsinas, 2022)
As a means of transportation between islands, sea transportation has the advantage of being able to distribute goods with a larger capacity than other transportation, and also the cost of sea transportation is relatively cheaper than other crossing transportation. This is very effective for inter-island transportation purposes. In particular, Aceh Singkil and Pulau Banyak have experienced an increase in tourists. The location of this research is in Singkil District to Pulau Banyak District. This research is in the form of comparative analysis of sea transportation modes between ferries and fast boats. The analytical method used is descriptive analysis and multiple linear regression. The variables in this study are travel costs (X1), departure schedule (X2), security and safety (X3) and mode selection variable (Y). Based on data processing the travel costs are in accordance with the costs desired by consumers, namely -0.022 for Ferries and 0.011 for Fast Boats, the departure schedule for Ferries is increased by obtaining a value of 0.879 and the safety security of Fast Boats is increased by obtaining a value of 0.920. So the Ferry Ship must be upgraded to Departure Schedule while the Fast Ship must be upgraded to the Safety and Security Factor.